KEY DETERMINANTS AND TRENDS OF THE “SHADOW ECONOMY” IN UZBEKISTAN - Karimov Diyor Mukhtarovich; Vahabjanova Jamilaxon Vosidjonovna (Journals Park Publishing, 2023)
The shadow economy, as a sign of informal and often illegal economic activity, is a phenomenon that has profound implications for both developed and developing countries. The global landscape of the shadow economy is characterized by its ability to adaptto changing circumstances, and Uzbekistan is no exception. Current trends in the country's informal sector demonstrate a complex pattern of economic activity that often goes beyond formal regulation and reporting mechanisms. From small businesses operating in the shadows to informal operations, the nuances of these trends are explored to provide a comprehensive understanding of the scale and nature of the country's shadow economy. This article examines current trends in the development of the shadow sector in the Republic of Uzbekistan, and examines the main determinants and potential consequences of the shadow economy in the context of the country.
Keywords: shadow economy, determinants, tax burden, state regulation, development of the official economy, smuggling of goods.